2019
DOI: 10.17503/agrivita.v41i3.2435
|View full text |Cite
|
Sign up to set email alerts
|

Size Classification of Tomato Fruit Using Thresholding, Machine Learning, and Deep Learning Techniques

Abstract: The size of tomato fruits is closely related to the market segment and price. Manual sorting in tomato is very dependent on human interpretation and thus, very prone to error. The study presents thresholding, machine learning and deep learning techniques in classifying the tomato as small, medium and large based from a single tomato fruit image implemented using Open CV libraries and Python programming. Tomato images with different sizes are gathered where features like area, perimeter and enclosed circle radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…NPK, iron, and salinity concentration were previously optimized based on germination rate and root morphology for lettuce and rice [6]- [8]. Crops, such as corn, rice, tomato, and lettuce, are vulnerable to climate change resulting in lower biomass production [5], [9], [10]. The initial tendency to improve crop quality is through adjusting the irrigation and fertigation [11], air velocity [12], and spectral filters [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NPK, iron, and salinity concentration were previously optimized based on germination rate and root morphology for lettuce and rice [6]- [8]. Crops, such as corn, rice, tomato, and lettuce, are vulnerable to climate change resulting in lower biomass production [5], [9], [10]. The initial tendency to improve crop quality is through adjusting the irrigation and fertigation [11], air velocity [12], and spectral filters [13].…”
Section: Introductionmentioning
confidence: 99%
“…Current optimization approaches make use of crop features such as fresh weight and leaf shape index [29], dry biomass [30], carotenoid [31], stomatal conductance, size, and density [32], leaf starch content [24], root anatomy [33], and vitamin C and nitrate content [15]. Image phenotyping has been made possible through computer vision (CV) [5], [9]. The use of adaptive neuro-fuzzy inference systems (ANFIS) [1] and genetic algorithm (GA) [2] have been proven effective in optimizing nonlinear relationships of environmental stressors to canopy areas.…”
Section: Introductionmentioning
confidence: 99%
“…Cultivation of vegetable crops inside a controlled environment chamber and extracting leaf canopy signatures that holds essential information for crop phenotyping has captivated agriculturist and scientist for quite a few generations (Burgos-Artizzu, Ribeiro, Guijarro, & Pajares, 2011;Calangian et al, 2018;de Luna, Dadios, Bandala, & Vicerra, 2019;Hang, Lu, Takagaki, & Mao, 2019;Loresco, Valenzuela, Culaba, & Dadios, 2019;Zou et al, 2019). In this study, it is shown that indoor hydroponic lettuce canopy area can be measured based on numerical image textural feature analysis of Haralick and gray level co-occurrence matrix (Table 1) as compared with morphological pixel feature (Calangian et al, 2018), leaf shape (Saleem, Akhtar, Ahmed, & Qureshi, 2019) and point cloud analysis (Berk, Stajnko, Belsak, & Hocevar, 2020).…”
Section: Results Of Thresholding For Image Segmentation On Lettucementioning
confidence: 95%
“…Broader leaf corresponds to maturity as part of its phenological development. Several studies have already developed a non-destructive approach on estimating individual leaf area of carrot (Haug & Ostermann, 2015), cauliflower (Hamuda, Mc Ginley, Glavin, & Jones, 2017), cucumber (Xie et al, 2014), lettuce (Hernández-Hernández et al, 2016;Tian & Wang, 2009;Zou et al, 2019), maize (Burgos-Artizzu, Ribeiro, Guijarro, & Pajares, 2011), potato (Boyd, Gordon, & Martin, 2002), radish (Dang et al, 2018), sugar beet (Chebrolu et al, 2017) and tomato (Boulard, Roy, Pouillard, Fatnassi, & Grisey, 2017;de Luna, Dadios, Bandala, & Vicerra, 2019) considering the length and width of the leaf shape (Saleem, Akhtar, Ahmed, & Qureshi, 2019;Wang, Jin, Shi, & Liu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Opena et al [22] proposed an automated tomato classification system that used an artificial neural network (ANN) classifier and the artificial bee colony (ABC) algorithm used for training the model. Luna et al [23] proposed a classifier that is used to classify fruits in different classes based on size of images by thresholding, machine learning and deep learning models. Semary et al [24] proposed a method to classify infected fruits based on its external surface.…”
Section: State-of-the-art Fruit and Vegetable Image Classification Mementioning
confidence: 99%